2018
DOI: 10.1007/s00402-018-2868-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy of virtual surgical planning for patient-specific pre-contoured plate in acetabular fracture fixation

Abstract: Virtual surgical planning, patient-specific virtually pre-contoured plate template and 3D printing technology improve the outcomes of acetabular fracture surgery by reducing duration and invasiveness of surgery and improving the quality of reduction. However, studies with larger sample size are required to further validate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 18 publications
0
72
0
Order By: Relevance
“…However, virtual separation and reduction of the injured pelvis was a complicated and timeconsuming procedure for complex acetabular fracture. Maini et al [17] reported that the mean time required to contour one 3.5 mm reconstruction plate was approximately 4.4 min. Similar to these results, an average time of approximately 11.1 ± 3.4 min (range: 4-18 min) was spent on plate shaping in Group A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, virtual separation and reduction of the injured pelvis was a complicated and timeconsuming procedure for complex acetabular fracture. Maini et al [17] reported that the mean time required to contour one 3.5 mm reconstruction plate was approximately 4.4 min. Similar to these results, an average time of approximately 11.1 ± 3.4 min (range: 4-18 min) was spent on plate shaping in Group A.…”
Section: Discussionmentioning
confidence: 99%
“…Maini et al [ 17 ] reported that the mean time required to contour one 3.5 mm reconstruction plate was approximately 4.4 min. Similar to these results, an average time of approximately 11.1 ± 3.4 min (range: 4–18 min) was spent on plate shaping in Group A.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the benefits of 3D modelling and 3D printed aids for preoperative planning and templating of complex acetabular fractures 19–21. Maini et al , in a comparative study of 24 acetabular fractures, used a 3D modelling software and a 3D printer to create patient-specific (PSI) templates over which 3.5 mm reconstruction plates were manually contoured preoperatively and used for fixation 21. The results indicated that the patients of the PSI group had shorter mean time of surgery, less total blood loss and better anatomical reduction than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This enables an enhanced understanding of the anatomy and facilitates enhanced preoperative planning [11]. Several authors reported the benefits of 3D modeling and 3D printed aids for preoperative planning and templating of complex acetabular fractures [24][25][26]. Maini et al [25] evaluated the outcome patients with acetabular fractures, using a 3D modeling software and a 3D printer to create patient specific (PSI) templates over which 3.5-mm reconstruction plates were manually contoured preoperatively and used for fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the benefits of 3D modeling and 3D printed aids for preoperative planning and templating of complex acetabular fractures [24][25][26]. Maini et al [25] evaluated the outcome patients with acetabular fractures, using a 3D modeling software and a 3D printer to create patient specific (PSI) templates over which 3.5-mm reconstruction plates were manually contoured preoperatively and used for fixation. The results, compared with a non-PSI group of patients, indicated that the patients of the PSI group underwent to shorter time of surgery, less blood loss and better anatomical reduction.…”
Section: Discussionmentioning
confidence: 99%